ECONOMIC FEASIBILITY OF COMPOSITE FISH CULTURE IN LEASED-IN VILLAGE TANKS OF KANYAKUMARI DISTRICT - SURESH, R. (Journal of Indian Fisheries Association, 2015)
Kanyakumari district belonging to the high rainfall zone has resourceadvantages for composite fish culture in the leased-in village tanks. Thereare more than 400 fish farmers operating in leased-in tanks followingcomposite fish culture under the FFDA programme. To estimate theeconomic feasibility and financial viability of the enterprise, the presentstudy was taken up. 38 fish farmers selected from the district providedthe necessary information like capital investment, costs and return andconstraints. The data collected were analysed and a farm nearest to theaverage farm situation was taken as the representative farm. Investmentcriteria like PayBacl{ Period (PBP), Simple Rate ~f Returns (SRR), NetPresent Value (NPV) and Benefit Cost Ratio (BCR) were estimated takinginto account a period of 10 years, the period for which the village tanksare leased-out to fish farmers under the FFDA programme. The analysisindicated the profitability of composite fish culture in village tanks inthe district and the results are discussed with recommendations.